Nonlinear optical response of photochromic azobenzene-functionalized self-assembled monolayers - Schulze, Michael; Utecht, Manuel; Moldt, Thomas; Przyrembel, Daniel; Gahl, Cornelius; Weinelt, Martin; Saalfrank, Peter; Tegeder, Petra (Physical chemistry, chemical physics, 2015)
The combination of photochromic and nonlinear optical (NLO) properties of azobenzene-functionalized self-assembled monolayers (SAMs) constitutes an intriguing step towards novel photonic and optoelectronic devices. By utilizing the second-order NLO process of second harmonic generation (SHG), supported by density-functional theory and correlated wave function method calculations, we demonstrate that the photochromic interface provides the necessary prerequisites en route towards possible future technical applications: we find a high NLO contrast on the order of 16% between the switching states. These are furthermore accessible reversibly and with high efficiencies in terms of cross sections on the order of 10−18 cm2 for both photoisomerization reactions, i.e., drivable by means of low-power LED light sources. Finally, both photostationary states (PSSs) are thermally stable at ambient conditions.
Gesehen am 20.07.2020